Phase transformation mechanism of MnCO3 as cathode materials for aqueous zinc-ion batteries - Zheng, Junjie; Liu, Pengcheng; Yao, Jia; Gan, Yi; Li, Jingying; Wang, Cong; Liu, Xiang; Rao, Yiheng; Ma, Guokun; Lv, Lin; Wang, Hanbin; Tao, Li; et al. (Frontiers in Chemistry, 2022)
Aqueous rechargeable zinc ion batteries (ZIBs) have been paid more and more attention because of their high specific capacity, high safety and low cost. Reasonable design of Mn-based cathode materials is an effective way to improve the performance of ZIBs. Herein, a square block MnCO3 electrode material is synthesized on the surface of carbon cloth by one-step hydrothermal method. The phase transition of MnCO3 was accompanied by the continuous increase of specific capacity, and finally maintained good cycle stability in the charge discharge process. The maximum specific capacity of MnCO3 electrode material can reach 83.62 mAh g-1 at 1 A g-1. The retention rate of the capacity can reach 85.24% after 1500 cycles compared with the stable capacity (the capacity is 61.44 mAh g-1 under 270th cycle). Ex-situ characterization indicate that the initial MnCO3 gradually transformed into MnO2 accompanied by the embedding and stripping of H+ and Zn2+ in charge and discharge. When MnCO3 is no longer transformed into MnO2, the cycle tends to be stable. The phase transformation of MnCO3 could provide a new research idea for improving the performance of electrode materials for energy devices.